High-Resolution Ultrasound and Magnetic Resonance Imaging of Abnormal Ligaments in Thoracic Outlet Syndrome in a Series of 16 Cases - Jengojan, Suren; Bernathova, Maria; Moritz, Thomas; Bodner, Gerd; Sorgo, Philipp; Kasprian, Gregor (Frontiers in Neuroscience, 2022)
Introduction Neurogenic thoracic outlet syndrome (NTOS) is a complex entity that comprises various clinical presentations, which are all believed to result from mechanical stress to the brachial plexus. Causes for the stress can include fibrous bands, spanning from the transverse processes, stump, or cervical ribs to the pleural cupula. The aim of this case series is to document how the combined potential of high-resolution neurography, including high-resolution ultrasound (HRUS), and magnetic resonance imaging (MRI) can be used to identify, anatomical compression sites, such as stump ribs and their NTOS associated ligamentous bands. Materials and Methods Retrospective chart and image reviews identified patients, who underwent HRUS between 2011 and 2021 and the diagnosis of NTOS caused by accessory ligaments was subsequently confirmed by radiological imaging (MRI) and/or surgical exploration. Results Sixteen patients were included in this study. In all cases, a ligament extending from the tip of a stump rib to the pleural cupula could be depicted. In all cases, these structures led to compression of the lower trunk of the brachial plexus. All surgically explored cases confirmed the radiological findings. Conclusion This case-series demonstrates that HRUS and MRI can directly and reliably visualize accessory costocupular ligaments and a stump rib in patients with symptoms of NTOS. HRUS may be used as the first imaging modality with which to diagnose suspected NTOS.